Representatividade de matas ripárias na diversidade de aves da região da planície alagável do alto rio Paraná : implicações para a conservação. - Ramos, Camila Crispim de Oliveira (2010)
Forest fragmentation alters regional and local biodiversity patterns through loss of microhabitat, isolation of habitat and changes in the dispersion and migration patterns. Their deleterious effect on birds is felt mainly on the groups with specific ecological requirements. The relationship of these groups with greater sensitivity to fragmentation and the size of the area are directly proportional. However the preservation of large contiguous areas is not viable in many regions, mainly due to massive cattle farming. In this context the preservation of riparian forests can act as an alternative to increase the available forest areas and biodiversity. A study conducted in the upper Paraná River floodplain in the Paraná State, Brazil, evaluated the importance of two small riparian forests in maintaining the regional diversity of birds. The forest margin the river São Pedro has 4.5 ha and that one marging the Caracu Stream has 10 ha and both are connected to larger fragments of riparian corridors. The studie areas, showed a great ability to maintain high species richness (165 species in total, 128 and 145, respectively by area). It was found that species with small to medium body size, tolerance to edge, low sensitivity and insectivorous feeding habits are more likely to occupy such environments. In the River São Pedro and in the Caracu Stream representative portions we recorded 38.6% and 34% of the avifauna cited from of the upper Paraná River floodplain, respectively. The two riparian forests differ significantly to each other in the structuring of the community. Species forestry and foraging preferentially in the middle stratum prevailed in the forest with less anthropogenic influence. While those of open habitat or edge which feed on the ground prevailed in more impacted place. Thus, we can infer that in the study area the presence of riparian forest fragments of this nature is important for the conservation of the avifauna. Due to the absence of large fragments the forest portion of the regional landscape is represented by corridors of riparian forest, therefore the connectivity of the landscape is the determining factor for the high regional diversity.